The HIF prolyl hydroxylase PHD3 is a potential substrate of the TRiC chaperonin. - Masson, N; Appelhoff, R; Tuckerman, JR; Tian, Y; Demol, H; Puype, M; Vandekerckhove, J; Ratcliffe, P; Pugh, C (2004)
Hypoxia-inducible factor-1 (HIF) is regulated by oxygen-dependent prolyl hydroxylation. Of the three HIF prolyl hydroxylases (PHD1, 2 and 3) identified, PHD3 exhibits restricted substrate specificity in vitro and is induced in different cell types by diverse stimuli. PHD3 may therefore provide an interface between oxygen sensing and other signalling pathways. We have used co-purification and mass spectrometry to identify proteins that interact with PHD3. The cytosolic chaperonin TRiC was found to copurify with PHD3 in extracts from several cell types. Our results indicate that PHD3 is a TRiC substrate, providing another step at which PHD3 activity may be regulated.